Influence of Foundation Pit Excavation on Tunnels at Different Locations. (28th January 2022) - Wang, Chengwu; Sun, Huasheng; Zhang, Jihua; Lu, Yu
Abstract : To evaluate the tunnel deformation law and soil stress distribution between foundation pit excavation and tunnel in different locations, numerical analyses using the hypoplastic model are conducted based on reported centrifuge model tests. Two cases are designed to investigate the effects of the foundation pit excavation on the deformation of existing tunnels. In case C, an existing tunnel is directly located underneath the foundation pit; in case S, the tunnel is located at one side of the foundation pit. Three-dimensional tunnel deformation mechanisms along the tunnel axis are observed through the variation of stresses change in the soil circumambient tunnel. It is found that compared with case C, there are minor Earth pressure changes in case S. The different Earth pressure changes around the tunnel lead to different modes of tunnel deformation. The maximum additional tunnel bending strain appears at the crown and invert, while the minimum value appears at the spring lines in case C. In case S, the maximum values appear in the right shoulder and left knee, while the minimum values appear on the left shoulder and right knee. The additional tunnel bending strain and stress reduction at different tunnel cross sections in case S is much smaller than those in case C. In case C, after the excavation, lateral Earth pressure coefficient changes Δ K xz and Δ K yz rise to 70% and 150%, respectively, of their initial value at shoulders, while little changes can be found at spring lines. However, in case S, the maximum absolute value of both Δ K xz /( K xz )0 and (Δ K yz /( K yz )0 ) is no more than 10%.